Teacher’s Perception and Challenges in Using Video Animation to Teach Vocabulary to Students with Disabilities - Putri, Rizki Rahma; Prasetyarini, Aryati (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study investigates teachers' perceptions and challenges regarding the use of animated videos in learning vocabulary in English for students with disabilities. This research aims to find out the teachers' perceptions towards the use of animated videos in learning vocabulary in English and the challenges faced by teachers when using animated video media as a means of learning vocabulary in children with disabilities. Methodology: This study employed a qualitative methodology, triangulating data through interviews, classroom observations, and documentation. We conducted data analysis using Craswell's framework and Miles and Huberman's interactive model, which included data reduction, data presentation, and conclusion formulation. We purposefully selected three English teachers and corroborated the data with information from other sources to ensure its accuracy. The observation evaluated the application of video animation, the interview delved into teachers' perceptions of its use, and the document analysis scrutinized the involvement of students with disabilities in learning through video animation. Results: These findings show that according to teachers' perceptions, the use of animated videos in vocabulary learning is effective but depends on the condition and level of disability in students. Teachers also encounter challenges and difficulties when teaching vocabulary to students with disabilities using animated videos. Applications/Originality/Value: This study highlights teachers' views and obstacles in using video animation to teach disabled students vocabulary. It emphasizes the necessity for customized resources, teacher training, and flexible animation techniques to assist special needs student learning.